从吴明益《复眼人》看自然书写 = Nature writing in Wu Ming-Yi's the man with the compound eyes - 云嘉慧 Hoon, Jacinda Jia Hui (Nanyang Technological University, 2020)
本文主要以「自然书写」为切入点，讨论台湾作家吴明益的作品《复眼人》，并着重分析《复眼人》如何呈现出自然书写文学的特征。由于《复眼人》异于吴明益以往自然书写的风格，本文尝试解读他如何把自然万物与人类放在同等的位阶时，不忘透过不同人物带出隐含的生态环境概念。最后，本文试图探讨吴明益在《复眼人》传达出对自然的尊重和生态观，以及人与自然的关系，且勾勒出「复眼人」的意涵，并探究《复眼人》在当代台湾自然书写作品中的价值与意义。This paper utilises the concept of "Nature writing" to discuss Taiwanese writer Wu Ming-Yi's The Man with the Compound Eyes. It will analyse how he presents the characteristics of nature writing in the novel. Known for nature writing literature, Wu displays a different style in The Man with the Compound Eyes. While the foundation of the story is based on environmental issues, the novel reaches far beyond an ecological allegory. This paper will also attempt to interpret how Wu goes beyond nature writing through the lens of different characters in the book. Apart from exploring how Wu conveys his environmental message and respect for nature, this paper will seek to identify the hidden meaning of Wu's man with compound eyes and the significance of the novel amongst the other literary works of Taiwan's nature writing.